Implementasi Permen LHK No. 52 dan 53 Tahun 2019 di Lingkungan SDN 02 Sungai Naning dan SMPN 1 Bukit Barisan Kabupaten Lima Puluh Kota - Eflita, Yenti; Sulistyowati, Lilik; Adji, Sandra Sukmaning (LPPM Institut Pendidikan Nusantara Global, 2024)
The issuance of Minister of Environment and Forestry No. 52 and 53 of 2019, makes all schools have to implement it, with the aim of creating a representative learning environment that is fun and comfortable for students as an effort to form an environmentally caring character. Implementation of Minister of Environment and Forestry No. 52 and 53 of 2019 at SDN 02 Sungai Naning and SMPN 1 Bukit Barisan using several concrete steps, namely planning, organizing, implementing and controlling. The purpose of the study is to evaluate and describe planning, organizing, actuating, and control in implementing Minister of Environment and Forestry No. 52 and 53 of 2019 in the environment of SDN 02 Sungai Naning and SMPN 1 Bukit Barisan Kab. Fifty Kota. This research is a field type (field research) with qualitative methods, and the approach is descriptive analytics. The source of the data is research informants, in the form of primary data, namely the heads of SDN 02 Sungai Naning and SMPN 1 Bukit Barisan. The secondary data consists of the Head of the Education Office and the Head of the Ministry of Religion of Fifty City Regency, Vice principals, and students. Research instruments in the form of observation, interviews and documentation. Data analysis using reduction techniques, display verification and drawing conclusions. Test validity with credibility, dependability, capability and auditoring tests. Research results 1) Insightful policy planning, including issuing decrees (SK), forming an Adiwiyata implementation team, forming organizational structures, integrating with the school's vision and mission, and conducting mapping. Planning for an environment-based curriculum by integrating it into the curriculum, learning methods and models, participatory based environmental activity planning including mutual assistance, extracurricular scouts, making green houses, living pharmacies, hydroponics, planning infrastructure management including resource utilization, waste and waste management systems, building partnerships with related agencies. 2) Organizing includes division Job description in accordance with the organizational structure. 3) Implementation in the implementation of Minister of Environment and Forestry No. 52 and 53 by carrying out all parts of planning properly and correctly. 4) Control activities in the form of monitoring, inspection, supervision, and evaluation as well as projections for future maturity.